Kaposi sarcoma associated with HIV infection. - Miranda, A M (1999)
Kaposi's sarcoma is the most common neoplasm in AIDS patients. In a 12-year period, 45 (8%) cases were diagnosed in 552 patients with AIDS. Epidemiological and clinical aspects are reviewed. The disease occurred predominantly in males and homosexuals. In 30 (67%) patients it was the first manifestation of AIDS. Skin and/or oral disease was the most frequent manifestation observed in our patients; 13 (29%) had visceral involvement. Previous or concommitant opportunistic diseases, systemic illness and severe immunosuppression were present in the majority of the patients. Opportunistic infections were the cause of death in 30 patients; in five others, Kaposi's sarcoma was responsible for death. Advances in antiretroviral therapy were of benefit for patients submitted to chemotherapy and may contribute to a reduction in morbidity with this neoplasm.